2022
DOI: 10.3390/aquacj2010001
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Haemal Lordosis in European Seabass Dicentrarchus labrax (Linnaeus 1758)

Abstract: Lordosis of the haemal part of the vertebral column is a frequent abnormality in reared fish. Haemal lordosis develops during the late larval and early juvenile life stages of fish, mainly due to the high swimming activity of the fish in the rearing tanks. In the present study, we have examined whether haemal lordosis recovers during the growth of European seabass. Furthermore, we aimed to develop simple morphometric indices (PrAn1 and PrAn2) that might link the severity of lordosis at the juvenile stage with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Recovery potential, internally and externally, can reach up to 74.5% within a week after the induction of a severe case of lordosis. Complete normal vertebrae shape and non-inverted spine orientation observed in this study, are in accordance with the existing literature reporting a partial to complete recovery of the vertebral column in lordotic gilthead seabream (27% of the recovered individuals 11 ) and European sea bass (56% of the abnormal individuals 12 ). No permanent injuries are expected to occur in the recovered animal’s vertebrae, since internal bone structures can be remodeled back to normal (present study).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Recovery potential, internally and externally, can reach up to 74.5% within a week after the induction of a severe case of lordosis. Complete normal vertebrae shape and non-inverted spine orientation observed in this study, are in accordance with the existing literature reporting a partial to complete recovery of the vertebral column in lordotic gilthead seabream (27% of the recovered individuals 11 ) and European sea bass (56% of the abnormal individuals 12 ). No permanent injuries are expected to occur in the recovered animal’s vertebrae, since internal bone structures can be remodeled back to normal (present study).…”
Section: Discussionsupporting
confidence: 93%
“…In both cases, increased exercise conditions are reported as the stimuli and an interaction between muscle and bone of the haemal region is described as the response center of changes leading to lordosis. Regardless of the species, a transfer to less intense swimming environment seems to trigger the recovery of this specific deformity ( 11 , 12 , present study).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The increased severity of lordosis based on the angle of curvature was found to be significantly related with the number of affected vertebral centra in European seabass [49], therefore angular measurements can represent a reliable proxy for overall shape changes in the vertebral column. The classification of lordosis severity could also have useful applications for studies investigating recovery, due to recent findings that, in certain cases, affected fish can recover from lordosis [65][66][67]. In this current study, the classification of lordosis severity demonstrated that, at this life stage, gilthead seabream show a wide array of severity and that differences among the distributions of severity classes significantly differed in response to the density.…”
Section: Discussionmentioning
confidence: 54%